TPE‐conjugated biomimetic and biodegradable polymeric micelle for AIE active cell imaging and cancer therapy. Issue 1 (26th August 2017) - Zhuang, Weihua; Ma, Boxuan; Liu, Gongyan; Li, Gaocan; Wang, Yunbing
ABSTRACT: Smart nanocarrier for simultaneous drug delivery and cellular imaging is ideal for both cancer therapy and diagnosis. In this work, polymeric micelles based on the tetraphenylethene (TPE) conjugated poly( N 6‐carbobenzyloxy‐l ‐lysine)‐ block ‐poly(2‐methacryloyloxyethyl phosphorylcholine) (TPE‐PLys‐ b ‐PMPC) copolymer are successfully prepared. Such biomimetic and biodegradable TPE‐PLys‐ b ‐PMPC micelles exhibit remarkable aggregation‐induced emission (AIE) feature and great biocompatibility, showing great potential for bioimaging application. In addition, anticancer drug doxorubicin (DOX) can be incorporated into the core of micelles and the intracellular release of DOX can be furthermore traced through the fluorescent imaging of these AIE micelles. As expected, this DOX‐loading polymeric micelle shows significant growth inhibition against HeLa cells and 4T1 cells and such TPE‐PLys‐ b ‐PMPC micelles would be a promising drug carrier for potential cancer therapy and bioimaging. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45651. Abstract :